A computational study of ion speciation in mixtures of protic ionic liquids with various molecular solvents: Insight into the solvent polarity and anion basicity. Issue 3 (4th October 2016) - Huang, Jiayao; Fu, Aiping; Li, Hongliang; Li, Hao; Chu, Tianshu; Wang, Zonghua
Abstract: The ion pairing state of the ionic liquids greatly depends on the cosolvent which subsequently affects the properties and the functionalities. Density functional calculations have been performed to study the ion pairing formation process of protic ionic liquids (PILs) ([Et3 NH][CH3 SO3 ]/TEAMS or [Et3 NH][CF3 SO3 ]/TEATF) dissolved in different solvents. The clusters involving the cation, anion, and different number of solvent molecules have been used to simulate the contact ion pairs (CIPs) and the solvent‐separated ion pairs (SIPs) in the mixtures with varying solvent concentrations. The geometric, energetic data, and the natural bond orbital analysis suggest the smallest number of the water molecules required to break the TEAMS CIPs is four, while it is three for TEATF. This is consistent with the experimental prediction that if the mixture of TEAMS and water was replaced by TEATF and water, the transition process began at a lower water concentration. Furthermore, the calculated results also confirm that the weakly polar organic solvents favor the CIP form at all solvent concentrations, while the high polarity solvents promote dissociation of the CIP to generate the SIP form for particular PILs. The different separation nature of the given solvents can be interpreted in terms of their distinct hydrogen bond donor and acceptor abilities. Abstract : Understanding the relationship between the ion speciation of particular ionic liquids and their cosolvent with varying concentration and polarity is important for both fundamental research and practical applications. Density functional theory calculations provide an insight into the ion pairing formation process of protic ionic liquids dissolved in different solvents. The different separation nature of the solvents can be explained in term of their unique hydrogen bond donor and acceptor abilities.